If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8(x + -7) = 3x + -46 Reorder the terms: 8(-7 + x) = 3x + -46 (-7 * 8 + x * 8) = 3x + -46 (-56 + 8x) = 3x + -46 Reorder the terms: -56 + 8x = -46 + 3x Solving -56 + 8x = -46 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -56 + 8x + -3x = -46 + 3x + -3x Combine like terms: 8x + -3x = 5x -56 + 5x = -46 + 3x + -3x Combine like terms: 3x + -3x = 0 -56 + 5x = -46 + 0 -56 + 5x = -46 Add '56' to each side of the equation. -56 + 56 + 5x = -46 + 56 Combine like terms: -56 + 56 = 0 0 + 5x = -46 + 56 5x = -46 + 56 Combine like terms: -46 + 56 = 10 5x = 10 Divide each side by '5'. x = 2 Simplifying x = 2
| -8+4n=2(6-8n) | | (y+2)-y=2(y-1)+5 | | 3c^3-192=1 | | abs(-1+3x)=7x+4 | | 3(4k+5)=-27+6k | | 3/5x+2=6 | | 2y+3y=55 | | 4(4k+5)=-27+6k | | 3+4e= | | -8(8p+6)=8-8p | | 3+5e= | | 6-2(x+1)=42 | | 2x+1x=7 | | 12x-4=36 | | 6-4(n-1)=2n+4 | | 6(4x+2)+4x= | | 3(-7+3x)(-6-6x)= | | 18/7= | | 9x=3(7x+24) | | 3[x-1]=7 | | x+0.05(x)=9.70 | | graphy=-7x-13 | | (3x+13)+10= | | 8x^4-18x^2+8x^4=0 | | 1a^2+3a=-2 | | 2x-(3x/2)=4 | | 115=8/5x | | 3xsquared-7=69 | | kx^2-9x+6=0 | | 4x+6=2(4+x)-2 | | x-8=6x-6 | | 3x=4y+-8 |